THE CONCEPT OF DIGITAL STRESS AND ITS MANIFESTATIONS - Zayniddinova , Mukhlisa (Effective scientific journals, 2026)
This article provides a comprehensive psychological analysis of the concept of digital stress, a phenomenon that has become increasingly prevalent in contemporary society. The excessive flow of information, constant online availability, and intensive use of digital technologies exert significant psychological pressure on individuals, negatively affecting their emotional well-being and cognitive functioning. The study examines the main sources of digital stress, its psychological manifestations, and emotional–cognitive consequences using a systematic analytical approach. Analytical tables are employed to classify digital stressors and illustrate their impact levels. The findings highlight the importance of developing effective psychological prevention strategies and digital well-being practices to reduce digital stress in modern life.